Melancholia und Caritas: Humanität im Vorletzten – Bildwelten Lars von Triers und des frühneuzeitlichen Luthertums - Neddens, Christian (Game over?, 2017)
Lars von Trier’s movie Melancholia (2011) is a meditation on the book of Revelation. It is a celebration, majestically accompanied by sounds of Wagner, of the beauty of the end of a world, an end which is unavoidable and all-encompassing. The movie opposes the usual Western cinematic apocalypses, in which a few human beings are able to prevent, reverse, or escape the catastrophe. It destroy any optimism of progress. No movie by the Danish director is closer to the eschatology and ethics of early-modern Lutheranism, which was very keen on the “dear last day” (“liebe jüngste Tag”; Luther). On the basis of the view of life’s finite nature, there arose among Lutheran artists, poets and preachers a deep love of creation, of its vulnerability and beauty. This chapter presents and examines parallels between Lars von Trier’s movie and various artistic productions (images, poetry) from early modern Lutheranism, outlining common patterns of an ethos of existence under the sign of the penultimate.